Poverty's Deconstruction: Beyond the Visible - Sumon K. Bhaumik; Ira N. Gang; Myeong-Su Yun (Institute of Labor Economics (IZA), 2017)
In contrast to his contribution to other areas, Shubhashis Gangopadhyay's contributions to our understanding of poverty are often thought of as indirect consequences of the main themes of his work. Yet in more than 15 published papers Gangopadhyay directly takes on poverty, including its estimate and understanding its sources. Our contribution honours Gangopadhyay's work in this area by outlining an approach useful in deconstructing the changes and differences in the likelihood of poverty incidence. We highlight how far it can take us, and how it still leaves us far short of understanding much of what drives poverty.
Keywords: C20; I30; 330; poverty incidence; headcount ratio; capability approach; probit decomposition